(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article pays special attention to the importance of physical education in the education system, the role of sports in the formation of a healthy lifestyle and the role of sports in educating the younger generation. The global development of physical education and sports, the emergence of international competitions and their impact on society are also analyzed. This work, through an in-depth study of the historical processes in the field of physical education and sports, creates a basis for innovations and proposals that can be implemented in this area in the future. The article serves to further increase the importance of physical education and sports in the life of a person and society.